(untitled) (International Association of Biologicals and Computational Digest, 2022)
Tongue squamous cell carcinoma is the second most prevalent anatomic site of oral cancer in India which is associated with use of tobacco in various forms. p16INK4A a tumor suppressor gene and found inactivated by many mechanisms in cancer. This study role of p16 protein expression in tongue cancer patients. In this retrospective study, a total of 50 tongue cancer patients were enrolled. P16 protein was evaluated by immunohistochemistry on formalin fixed paraffin embedded tongue tumor tissues. Further, p16 protein expression was correlated with clinicopathological parameters and disease status. In this study, p16 expression was noted in 24% of tumor tissue of tongue cancer patients. In relation to clinical parameters, a significant higher p16 expression was seen in tobacco habituated patients. In relation with pathological parameters, a trend of higher p16 expression was noted in patients with T1 tumor size and poorly differentiated tumors. In univariate survival analysis, patients with p16 expression showed a trend of better diseases free survival and overall survival than patients with p16 negative expression. In summary, p16 overexpression can be considered as good prognosticator in tongue cancer. It may induce cellular senescence and thereby slower the tongue cancer growth.